Kształcenie pedagogów resocjalizacyjnych w systemie szkolnictwa wyższego = The education of rehabilitation educators in higher education system - Śliwa, Sławomir (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article concerns the issue of educating students of pedagogy specialising in rehabilitation. The author describes the nature of educating future rehabilitation educators in respect of legal regulations in the system of higher education. There follows a discussion on advantages and disadvantages of such solutions. There is also a description of research carried out among students and it further presents their opinions on the subject.
Keywords: kształcenie uniwersyteckie; pedagogika resocjalizacyjna; badania ankietowe; badania sondażowe